Caribbean Report 11-07-1990 - Crosskill, Hugh (anchor); Abrams, Elliot (interviewee); Bush, George; Khan, Sharief (correspondent); Jagan, Cheddi (interviewee); Norton, Michael (correspondent) (The British Broadcasting Corporation, 1990)
Reactions are still coming in to the recently announced initiative by the US president, George Bush, for partial relief of Latin American and Caribbean debt and their inclusion in a North American free trade area. The consequences of a free trade agreement between the US and Mexico for the Caribbean countries is also explored. Following the Financial News, in its fight for free and fair elections in Guyana, the Guyanese Action for Reform and Democracy (GUARD) is supporting moves by the opposition parties to form a common slate for the upcoming elections and urging the Commonwealth Secretary General to send an urgent mission to Guyana. Cheddi Jagan, opposition leader, is also meeting with Washington's senators and congressmen to ensure that an observer team led by Jimmy Carter is present during the upcoming Guyanese elections. The report concludes with a general strike being called in Haiti by the Unity Assembly to protest against the public reappearance of two former military leaders, Roger Lafontant and Williams Regala.
1. Headlines (00:00-00:46)
2. Elliot Abrams, former Assistant US Secretary of State for Latin American Affairs expresses concerns for the Caribbean should Mexico join the US free trade area (00:47-04:08)
3. Financial News. Excerpt of speech from US president, George Bush on the Uruguay Round of trade negotiations (04:09-05:41)
4. Cheddi Jagan, Guyana's opposition leader, visits Washington on the campaign trail in his quest for free and fair elections. Sharief Khan reports from Georgetown and Cheddi Jagan is interviewed (05:42-11:08)
Keywords: Trade -- Caribbean Area; Free trade -- Caribbean Area; Elections -- Guyana; Guyana -- Politics and government; General strikes -- Haiti; Elections -- Haiti; Guyanese Action for Reform and Democracy (GUARD); Lafontant, Roger; Regala, Williams